Estudio comparativo entre las herramientas libres de analisis y desarrollo staruml y fujaba para establecer la usabilidad y la aplicabilidad de la ingeniería inversa dentro del proceso de desarrollo de software en la empresa mercado Latacunga - Cepeda Vaca, Luis Orlando (2013)
Was developed with Open Source technology, namely that is free on the Internet. All development tools have been downloaded from the Internet, so we have starUML, Fujaba. The other tools used works under licenses purchased. This article sample a comparative study of the used tools for the process design, given their characteristics and the principal advantages, that helped to establish which have the best performance and provides the best services at the time of use. This work is part of investigation "Comparative study of analysis tools in software development", which will provide the appropriate selection medium according to the relevant features which determine the study, determining the feasibility of their use according to the benefits posed by each of them. We present general aspects of the work focused on certain engineering standards to be followed, then raises some functions of the groups that are part of the work team. Later discusses some practical cases in which techniques have been used and software engineering methods free. And finally, some conclusions.